The Role of Information Technology in Promotion Strategy. Case in Taman Mini Indonesia Indah and Ragunan, Indonesia - UNTARI, Dhian Tyas (Journal of Environmental Management and Tourism; Vol 11 No 4 (2020): JEMT Volume XI Issue 4(44) Summer 2020DO - 10.14505//jemt.11.4(44).20, 2020)
Jakarta is the capital city of Indonesia, one of the leading sectors is tourism. Tourism, which is one of the tertiary sectors, is the largest foreign exchange earner in Jakarta. Two Jakarta tourism icons are Ragunan and Taman Mini Indonesia Indah (TMII). Promotion is needed to maintain the stability of the number of visits in both tourist destinations, especially through the internet. Globalization brings people's behavior to information search patterns through the internet. Here is the problem you want answered; how effective are these two tourist sites on the perceptive perspective of the community. The aim of this study is to analyze the effectiveness of the Taman Mini Indonesia Indah (TMII) and Ragunan tourism Web. This is a quantitative research, using a sample of 165 people taken randomly from leading tourist attractions in DKI Jakarta, namely TMII and Ragunan. Dimensions used in research are empathy, persuasion, impact, and communication.